Development of carboxymethylcellulose based composites for bone tissue engineering. Issue 2 (29th June 2021) - Priya, Ganesan; Kumar, Uttamchand Narendra; Madhan, Balaraman; Manjubala, Inderchand
Abstract : The present study focuses on the development of carboxymethylcellulose (CMC)–biphasic calcium phosphate (BCP) composite scaffolds through the freeze-drying process for bone tissue engineering applications. Citric acid or fumaric acid was added as the cross-linker of CMC to improve the stability of composite scaffolds. The effect of change in freezing temperature (−20, −40 or −80°C) on the pore morphology, swelling ability and mechanical properties of composite scaffolds was studied. Cross-linked scaffolds showed an increased thermal degradation temperature compared with non-cross-linked scaffolds. All the composite scaffolds showed a porous structure with homogeneous blending of CMC and BCP. Cross-linked scaffolds showed appreciable swelling ability and stability in phosphate-buffered saline, while non-cross-linked scaffolds were unstable for 24 h. Cross-linked scaffolds had lower compressive strength than non-cross-linked scaffolds under dry conditions. However, in the hydrated state, only citric acid-cross-linked scaffolds were stable with improved compressive strength of 64 ± 4, 57 ± 4 and 67 ± 4 kPa when processed at −20, −40 and −80°C, respectively. Furthermore, three-dimensional culture of Saos-2 cells on citric acid-cross-linked scaffolds showed their suitability for cell proliferation and osteogenic differentiation. Therefore, citric acid-cross-linked CMC–BCP composite scaffolds may be promising scaffolds for bone tissue engineering applications.